DIDACTIC ASPECTS OF LITERARY TEXT STUDYING WITHIN ELEMENTARY SCHOOL CLASSES - GOLUBIŢCHI, Silvia (Acta et Commentationes, Sciences of Education, 2019)
Text study emphasizes literary code deciphering. There are various types of literary texts, each with a variety of approaches to be explored within classes. Each class begins with a preparatory activity in the text world, followed by text reading that stipulates the next conditions: reading condition as event, lecturer’s condition as performance, condition of poetic text as a work, condition of interpretation as an act of comprehension and recreation. Any text deciphering has at its basis two operations: comprehension and interpretation.